Recent advances in biomarkers for diabetes mellitus and tuberculosis comorbidity: a comprehensive review - Fang, Lihua; Wu, Yuqian; Fang, Xiaokang; Ning, Jie (Frontiers in Endocrinology, 2025)
Diabetes mellitus (DM) and tuberculosis (TB) are significant global health challenges that complicate diagnosis, treatment, and management due to their interrelated nature. DM increases TB risk and worsens outcomes, highlighting the need for early detection and effective management. This review summarizes recent advancements in biomarkers for DM-TB comorbidity, including microbial, metabolic, immunological, inflammatory, clinical, and genetic markers. We identified 30 relevant studies, through a literature search using keywords related to DM, TB, and biomarkers. Key findings include specific gut microbiota genera and lipid mediators that show promise for early diagnosis and treatment. Immunological biomarkers like altered CD8+ T cells and NK cells provide insights into disease severity and treatment monitoring. Inflammatory markers such as elevated CRP, ferritin, and IL-6 reflect heightened inflammation and could guide treatment strategies. Clinical biomarkers, including serum CA-125 (sensitivity 88.14%, specificity 95.83%) and AUC/MIC ratios of anti-TB drugs (e.g., moxifloxacin ≥67; sensitivity 97.3%, specificity 90.0%), demonstrate high diagnostic accuracy. Future research should focus on validating these biomarkers across diverse populations and integrating them into clinical practice to enhance DM-TB management and contribute to global disease control efforts.